CER 2019
DOI: 10.7176/cer/11-8-06
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-Induced Volumetric Shrinkage Characteristics of Highly Expansive Tropical Black Clay Treated with Groundnut Shell Ash for Barrier Consideration

Abstract: Contamination of underground water as a result of excessive crack on clay liner material is a prevalent phenomenon in an engineered landfill. Volumetric shrinkage strain (VSS) is one of the veritable properties considered for selection of materials suitable for liners and cover in waste containment systems. Material devoid of excessive shrinkage and cracking during climate change could possibly make a better barrier material that will eventually limit or control infiltration of leachate in an engineered landfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is important to note that the amendment of soil with non-conventional ameliorants which are sustainable and economical, has proved to be very successful due to their ability to perform anticipated outcomes in the geotechnical parameters of soft clay soil compared to conventional ameliorants. Thus, the emerging advances in construction materials have proved that diverse ameliorants rich in alumina and silica such as sawdust ash-quarry dust 5 , cement kiln dust-rice husk ash 6 , cement kiln dust-metakaolin 7,8 , cement kiln dust 9 , periwinkle shell ash 10 , oyster shell ash 11,12 , quarry dust 13 , marble dust-rice husk ash 14 , coconut husk ash 15 , corncob ash 16 , locust bean waste ash 17,18 , groundnut shell ash [19][20][21] , lime-rice husk ash 22 , bambara nut shell ash 23 , yam peel ash 24 , metakaolin 25 , mine tailings 26 , palm bunch ash 27 , cement kiln dust-periwinkle shell ash 28,29 , cow bone ash-waste glass powder 30 , sawdust ash-lime 31 , rice husk ash-sisal fibre 32 , coffee husk ash 33 , construction waste 34 , sawdust 35 , nanosilica 36 , electric arc furnace dust 37 , iron ore tailing 38 and so on have been utilised in the amendment studies of deficient soils and concrete structures. Conclusively, as a result of the positive outcomes recorded by the incorporation of solid wastes in soil amelioration studies, a comprehensive review was carried out on the trends in expansive soil stabilization using calcium-based stabilizer materials 39 .…”
Section: Role Of Extreme Vertex Design Approach On the Mechanical And...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the amendment of soil with non-conventional ameliorants which are sustainable and economical, has proved to be very successful due to their ability to perform anticipated outcomes in the geotechnical parameters of soft clay soil compared to conventional ameliorants. Thus, the emerging advances in construction materials have proved that diverse ameliorants rich in alumina and silica such as sawdust ash-quarry dust 5 , cement kiln dust-rice husk ash 6 , cement kiln dust-metakaolin 7,8 , cement kiln dust 9 , periwinkle shell ash 10 , oyster shell ash 11,12 , quarry dust 13 , marble dust-rice husk ash 14 , coconut husk ash 15 , corncob ash 16 , locust bean waste ash 17,18 , groundnut shell ash [19][20][21] , lime-rice husk ash 22 , bambara nut shell ash 23 , yam peel ash 24 , metakaolin 25 , mine tailings 26 , palm bunch ash 27 , cement kiln dust-periwinkle shell ash 28,29 , cow bone ash-waste glass powder 30 , sawdust ash-lime 31 , rice husk ash-sisal fibre 32 , coffee husk ash 33 , construction waste 34 , sawdust 35 , nanosilica 36 , electric arc furnace dust 37 , iron ore tailing 38 and so on have been utilised in the amendment studies of deficient soils and concrete structures. Conclusively, as a result of the positive outcomes recorded by the incorporation of solid wastes in soil amelioration studies, a comprehensive review was carried out on the trends in expansive soil stabilization using calcium-based stabilizer materials 39 .…”
Section: Role Of Extreme Vertex Design Approach On the Mechanical And...mentioning
confidence: 99%
“…The ANOVA computation of partial sum-of-squares and R-sqd. Statistics calculation results are presented in Tables 18,19,20,21,22,23. From the statistical analysis results, the model p-value of 0.0001 was derived for the three response variables while F-value of 77.67, 28.04, and 64.61 were obtained for CBR, UCS and RLS responses respectively. The indication of this statistical result showed that the derived model terms are statistically significant.…”
Section: Development Formulation and Validation Of The Extreme Vertex...mentioning
confidence: 99%
“…The mentioned challenges have triggered an examination into the stabilizing potential of sustainable materials such as waste plastic strips and sisal fiber for flexible pavement applications. On the other hand, Challenges associated with deficient soils that fail to meet certain engineering requirements, for its application as construction materials in flexible pavements has significantly increased the cost of roads construction in such areas [2][3][4][5]. These challenges necessitate the complete elimination of the entire soil in such areas and substituting it with a granular soil that has better bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Water content during soil compaction affects desiccation cracking. Lower water content balanced with higher compaction energy can minimize the potential for desiccation cracking (Cheng et al, 2021;Moses et al, 2019). Many researchers have demonstrated that the wetting-drying cycle applied to the soil liner exhibits a relatively constant hydraulic conductivity (Emmanuel & Anggraini, 2020;Ivoke et al, 2021;Mazzieri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%